Improvement of financial results budgeting in the CSR contents - Khachatryan, Qnarik (Bulletin of Yerevan University G: Economics, 2024)
Budgeting for financial results has traditionally been considered the preparation of cost and revenue estimates with responsibility centers in an organization. However, currently it covers a wider range, taking into account not only the internal but also the external value chain of the business. Currently, the value of organizations is not only evaluated by financial indicators, but also takes into account the responsibility of business from the point of view of ensuring public interests. The article makes recommendations for budgeting improvement of financial results, based on the requirements of companies  corporate social obligations.
Keywords: revenues and expenses; estimates; budgeting; sustainable development; business value chain; responsibility centers; corporate social responsibility